2019
DOI: 10.1021/acschemneuro.9b00436
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Intranasally Administered Deferoxamine in Rat Brain Tissue with Mass Spectrometry

Abstract: Deferoxamine, a metal chelator, has been shown to be neuroprotective in animal models of ischemic stroke, traumatic brain injury and both subarachnoid and intracerebral hemorrhage. Intranasal deferoxamine (IN DFO) has also shown promise as a potential treatment for multiple neurodegenerative diseases, including Parkinson’s and Alzheimer’s. However, there have been no attempts to thoroughly understand the dynamics and pharmacokinetics of IN DFO. We developed a new high-performance liquid-chromatography electros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…The targeted delivery of drugs to the central nervous system (CNS) through IN administration circumvents the blood‒brain barrier (BBB), which minimizes systemic exposure and reduces associated adverse effects. It has been previously demonstrated that intranasal administration increased the targeting of DFO to the brain compared to intravenous delivery [ 39 ]. In our study, DFOM was dissolved in pyrogen-free normal saline solution and administered intranasally three times a week at a dose of 100 mg/kg.…”
Section: Discussionmentioning
confidence: 99%
“…The targeted delivery of drugs to the central nervous system (CNS) through IN administration circumvents the blood‒brain barrier (BBB), which minimizes systemic exposure and reduces associated adverse effects. It has been previously demonstrated that intranasal administration increased the targeting of DFO to the brain compared to intravenous delivery [ 39 ]. In our study, DFOM was dissolved in pyrogen-free normal saline solution and administered intranasally three times a week at a dose of 100 mg/kg.…”
Section: Discussionmentioning
confidence: 99%
“…The long-term prognosis for primary PCI and external CABG is similar, but the average length of hospital stay for PCI is shorter. In addition, a large number of modern clinics do not always have the opportunity to accept a patient urgently for surgery (Fan et al, 2021;Kosyakovsky et al, 2019). Therefore, it is necessary to develop simple clear criteria for selecting patients with acute myocardial infarction for emergency surgical revascularization.…”
Section: Introductionmentioning
confidence: 99%